2018
DOI: 10.1007/s12291-018-0751-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-581-Related Single Nucleotide Polymorphism, rs2641726, Located in MUC4 Gene, is Associated with Gastric Cancer Incidence

Abstract: MUC4 is aberrantly expressed in several carcinomas including breast, colon, ovarian, lung, prostate, stomach and pancreatic cancers. MUC4 can regulate cell apoptosis negatively and facilitate stomach tumorigenesis. In this research, we aimed to evaluate the possible association between rs2641726 (C [ A) polymorphism of MUC4 and gastric cancer risk in the Iranian population. In this case-control study, we collected blood samples from 168 gastric cancer patients and 66 healthy subjects. Allelespecific primer pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…However, the results of several studies suggest that the dysregulation of miR-581 is involved in the development of cancer. For example, miR-581-associated single-nucleotide polymorphisms located on the MUC4 3 UTR may reduce the interaction between miR-581 and MUC4 mRNA, promote the expression of oncoprotein MUC4, and be associated with the incidence of gastric cancer [21]. Additionally, miR-581 is down-regulated in patients with hepatocellular carcinoma (HCC) and can be used as a novel marker for tumors and chronic liver disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of several studies suggest that the dysregulation of miR-581 is involved in the development of cancer. For example, miR-581-associated single-nucleotide polymorphisms located on the MUC4 3 UTR may reduce the interaction between miR-581 and MUC4 mRNA, promote the expression of oncoprotein MUC4, and be associated with the incidence of gastric cancer [21]. Additionally, miR-581 is down-regulated in patients with hepatocellular carcinoma (HCC) and can be used as a novel marker for tumors and chronic liver disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…While dietary regime and lifestyle are the most recognized factors, enhanced identi cation of the genetic risk factors is expected to improve the understanding of the basic molecular events involved in tumorigenesis [25] . Genetic factors, including gene expression pro le and cancer biomarkers, such as SNPs, have a crucial role in improving the early diagnosis of GC [26] .…”
Section: Discussionmentioning
confidence: 99%
“…We found that circ_ASPH was overexpressed in CCA cells and facilitated cell proliferation and metastasis by regulating the miR‐581/ABCG1 signaling. The tumor suppressor role of miR‐581 has previously been observed in several cancers [5, 6]. Zhang et al [6].…”
Section: Figurementioning
confidence: 99%